Mechanoregulation of Cell Fate by Low-intensity Pulsed Ultrasound: Mechanisms and Advances in Regenerative Medicine - Lingling Lei; Qing Zhang; Meng Du; Li Li (BIO Integration)
As a mechanical wave capable of transmitting thermal and mechanical energy, ultrasound has emerged as a pivotal tool in regenerative medicine due to its non-invasive nature. Low-intensity pulsed ultrasound (LIPUS), a mechanoregulatory technique independent of thermal effects, delivers controlled mechanical stimuli to activate endogenous mechanotransduction pathways, such as ion channels, transmembrane proteins, and cytoskeleton-mediated signaling cascades. These pathways regulate critical cellular processes, such as proliferation, differentiation, and apoptosis, positioning LIPUS as a promising modality for targeted modulation of cell fate. Preclinical and clinical studies have demonstrated the therapeutic efficacy of LIPUS across diverse applications, including bone repair, neural regeneration, and soft tissue rehabilitation. However, optimizing stimulation parameters and advancing clinical translation remain key challenges. This review summarizes the central role of LIPUS in promoting tissue regeneration through non-thermal regulation of cellular homeostasis and explores strategies to accelerate clinical adoption of LIPUS. By integrating mechanistic insights with translational perspectives, this review provides a roadmap for advancing LIPUS-driven regenerative medicine in the era of precision bioengineering.